Assessing impact of varied social and ecological conditions on inherent vulnerability of Himalayan agriculture communities. Issue 10 (25th November 2020) - Chauhan, Neha; Shukla, Roopam; Joshi, P. K.
Abstract: Threats of changing climatic conditions on Himalayan agriculture communities are well established and observed. predisposed marginalized social and fragile ecological conditions have increased vulnerability of these communities. However, as vulnerability varies spatially and is effected by the bio-geographical conditions, the information on vulnerability distribution among the different biogeographic zones (BZs) is of value. This study aims to assess impact of social and ecological dimensions on vulnerability of agricultural communities in different biogeographical zones of Himalaya. Inherent vulnerability in different BZs was assessed at village level by performing hierarchal additive clustering. A total of 39 indicators (16 for ecological and 23 for social) were considered and weighed by Analytical Hierarchal Process (AHP). The spatial distribution of different vulnerability indices was analyzed by Global and Local Moran's Index. The results show presence of very high social vulnerability (0.71 ± 0.11) for middle Himalayas (BZ2) and higher ecological vulnerability (0.68 ± 0.13) for lower Himalayas (BZ1). Among the different zones, middle Himalayas (BZ2) shows the maximum inherent vulnerability. The present study aids the policy-makers and stakeholders in identifying the regions requiring immediate intervention. The study also highlights the factors among social or ecological dimensions which require greater attention than others.